Tree of hope - Littlesugar, Amy (Philomel Books, 1999)
Florrie's daddy used to be a stage actor in Harlem before the Depression forced the Lafayette Theater to close, but he gets a chance to act again when Orson Welles reopens the theater to stage an all-black version of Macbeth.